Growth‐enhanced salmon modify stream ecosystem functioning. Issue 6 (19th October 2021) - Cucherousset, Julien; Sundt‐Hansen, Line E.; Buoro, Mathieu; Závorka, Libor; Lassus, Rémy; Bækkelie, Knut A. E.; Fleming, Ian A.; Björnsson, Björn Thrandur; Johnsson, Jörgen I.; Hindar, Kjetil
Abstract: Use of fast‐growing domesticated and/or genetically modified strains of fish is becoming increasingly common in aquaculture, increasing the likelihood of deliberate or accidental introductions into the wild. To date, their ecological impacts on ecosystems remain to be quantified. Here, using a controlled phenotype manipulation by implanting growth hormone in juvenile Atlantic salmon ( Salmo salar ), we found that growth‐enhanced fish display changes in several phenotypic traits known to be important for ecosystem functioning, such as habitat use, morphology and excretion rate. Furthermore, these phenotypic changes were associated with significant impacts on the invertebrate community and key stream ecosystem functions such as primary production and leaf‐litter decomposition. These findings provide novel evidence that introductions of growth‐enhanced fish into the wild can affect the functioning of natural ecosystems and represent a form of intraspecific invasion. Consequently, environmental impact assessments of growth‐enhanced organisms need to explicitly consider ecosystem‐level effects.